Pengaruh Profitabilitas, Leverage, Inflasi dan Suku Bunga terhadap Financial Distress dalam Masa Pandemi Covid-19 - Muhammad Fadhil Al Amin; Raudhatul Hidayah (Syntax Corporation, 2023)
This study analyzes the relationship between profitability, leverage, inflation and interest rates with financial distress in manufacturing companies listed on the IDX during the Covid-19 pandemic, namely during 2019-2021. The population in this study are all manufacturing companies listed on the IDX for the 2019-2021 period. Data obtained through the website idx.co.id. From the purposive sampling results, there were 66 companies that met the criteria. In this study using logistic regression analysis because there is a dummy variable in the dependent variable. This study uses the SPSS software test tool version 21. Based on the results obtained, profitability has a negative and significant impact on financial distress. The higher the profitability, the smaller the level of financial risk in a company. This is because the effective use of company assets will minimize company costs, enabling them to save funds and manage their business more efficiently. Leverage also has a significant effect on financial distress. Low corporate debt will minimize the risk of financial distress that will be borne by the company